Marketing India as a Brand (Brand India, an Idea Whose Time has Come) - Vernekar, Sachin S.; Wadhwa, Preety (Indian Journal of Marketing, 2009)
Many countries in the world can be identified as brand like: Germany for Automobiles, Japan for Technologies, Britain for its history, France for its culture, wines, perfumes and fashion and Middle East for its petroleum reserves, Switzerland for its dairy products, Scotland for its whisky, Italy for its sense of good food and high fashion and so on. Now what to associate India with, is it a democratic alternative to China or a Fast growing free market economy or can it be identified with the people with best brain or the birth place of great entrepreneurs like Tata’s, Mittal’s, Murthy, Premji, Birla’s, Ambani’s or India is like an onion which contains several layers, or is like jingoism, we should keep murmuring "MERA BHARAT MAHAN". On the other side Brand India can be looked as an entity, very broadly could be clustered as having the following characteristics: It is multi layered- by caste, by language, by income, which is actually of particular relevance to the marketers. It is constantly evolving Brand with a widely varying Diaspora of population, which makes it a challenge and often a nightmare for the brands. It is a country and a brand in transition-ever growing and undergoing transformation constantly, on various attributes. In the last 15-20 years, The Brand India has grown by leaps and bounds. The income levels of the people have gone up; spending propensity as well as the purchasing power has increased. Indians are spending like never before. Over the years, we have also witnessed Brand India becoming increasingly distorted in the absence of efforts to manage and develop its associations. The only obvious way out is branding or rather Re- Branding India.This paper will focus on various steps in the journey of positioning and repositioning India as a Brand and try to analyze the core competencies required to provide a base for building Brand India. This paper tries to explain the analogy between country and a brand; it also explains the concept of taking India as a Brand as well as positioning and repositioning brand India, Metamorphosis of India’s Image, and attempt has also been made to explain the progress India has made in the key areas like Economy and Business etc. At the same time it also pinpoints the major impediments in its journey to become a global brand.